The file and the witness. Analysis of the relation between memory and justice from the colombian case (2019)
In memory studies and in the field of transitional justice, the story of the victims is usually seen as relevant. It is usually assumed that what is said by the victims has an absolute value of truth and cannot be controverted, otherwise we would be attac